Some aspects of chemical composition of geological structure of "antropogenic lake district" - Jachimko, Barbara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The research results of some aspects of soil chemical composition in the surroundings of the biggest pit, acid reservoir located on Łuk Mużakowski (SW Poland) are presented. Samples were taken every 1m depth, from three 25m deep, boreholes and content of TOC, iron, calcium and aluminium was analyzed. Boreholes were located in the closest neighbourhood of the reservoir, one on side of groundwater inflow, two others on the opposite site. Watertable in each places was confined and groundwater had the chemical composition typical for AMD. Geological structure consisted mainly from sand and clay with sand and brown coal layers.
Keywords: zakwaszenie gleby; skład chemiczny gleby; zbiornik pokopalniany; Łuk Mużakowa; AMD; soil acidification; soil chemical composition